The Adventurous in Digital Space: From the Typewriter to E-Mail - Hernández y Hernández, Denise (2016)
In this study, we analyzed the history of the first contact of a group of graduate students in Barcelona, Spain, with Information and Communication Technologies (ICT) which includes the typewriter, computer, the Internet, and email. Data provided in this research were collected through interviews designed to recover information regarding: the student’s first experience with computers, the mechanisms used to learn how to use them, whether they learnt by themselves or were guided by an instructor, and the student’s age at the beginning of this process. We also were interested in understanding the learning process with email accounts: the first time students opened their accounts, whether students received or not assistance, and how did they find out what an email account was.  Finally, we recovered their opinions about the ICT.